An investigation of the adoption of green ICT in IIUM communities towards sustainable environment - Masud, Mosharrof Hussain; Abdul Malik, Noreha (Publications International Lahore, Pakistan, 2014)
Information and Communication Technology (ICT) plays a key role in the development and the sustainability of the modern life. It brings numerous benefits and facilities to the society and users. However, the usage of the ICT devices and its entire life cycle produce hazardous substances including harmful CO2. Reducing the energy consumption in an individual or organizational level effected the ultimate reduction of CO2 in global perspective. Therefore, the adoption of green ICT is becoming more popular due to the increasing number of ICT infrastructures and facilities. Considering this issue in mind, this paper addresses the scenario of energy consumption in the field of ICT in a global context. Particularly, an awareness survey has been conducted among staff and students of International Islamic University Malaysia (IIUM) to assess the adoption trend of green ICT in campus. Public awareness is considered one of the most important factors to increase the adoption of green ICT in everywhere. During the group survey, a short briefing and discussion also have been conducted to inform and motivate the students about green ICT. The survey results show that some interviewees are still not familiar with this “green ICT” term and its adoption. Therefore, further motivation and influence need to be drawn among staff and students towards a sustainable environment.